2020
DOI: 10.1109/tpel.2020.2976145
|View full text |Cite
|
Sign up to set email alerts
|

Power Electronic Pulse Generators for Water Treatment Application: A Review

Abstract: Water treatment is one of the most important issues for all walks of life around the world. Different from the conventional water treatment technology, the advanced power electronic pulse technology has unique features and advantages for the modern water treatment. Unfortunately, there is no literature reported to describe them in a comprehensive and systematic way. To fill this gap, an overview of modern power electronic pulse generators (PPGs) for water treatment is presented. This paper, for the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…In [21], a historical account of the development of Marx circuit and synchronous isolated driving techniques for switches is provided, it solely focuses on Marx type generators. In [9], a review of research on solid-state generators based on inductive energy storage and semiconductor opening switches (SOS) is presented, while in [22], pulse generators for water treatment applications are reviewed. However, there is still a lack of a comprehensive overview encompassing the various power electronics intensive HVPG topologies for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], a historical account of the development of Marx circuit and synchronous isolated driving techniques for switches is provided, it solely focuses on Marx type generators. In [9], a review of research on solid-state generators based on inductive energy storage and semiconductor opening switches (SOS) is presented, while in [22], pulse generators for water treatment applications are reviewed. However, there is still a lack of a comprehensive overview encompassing the various power electronics intensive HVPG topologies for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, many traditional methods create unwanted products in addition to water purification, or there are restrictions on their use. One of the new methods for using in water purification is the pulse power system method, which uses high voltage pulses to purify water in a short time (Akiyama et al , 2007; Guo et al , 2020; Sugai et al , 2010; Suzuki et al , 2011). The pulsed high voltage application in this system can cause some reactions in the treated material.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, physical water treatment technologies have developed rapidly, and the EF among them has been widely applied as a physical catalytic method. The combination of an external EF and flotation technology has provided a new field. Murugananthan et al studied a method of separating hydrophobic solid particles by electrolytic air flotation, which showed that the new method has higher separation efficiency than the traditional method.…”
Section: Introductionmentioning
confidence: 99%